Species-Specific Immunological Reactivities Depend on the Cell-Wall Organization of the Two Aspergillus, Aspergillus fumigatus and A. flavus - Wong, Sarah Sze Wah; Venugopalan, Lakshmi Prabha; Beaussart, Audrey; Karnam, Anupama; Mohammed, Mohammed Razeeth Shait; Jayapal, Jeya Maheshwari; Bretagne, Stéphane; Bayry, Jagadeesh; Prajna, Lalitha; Kuppamuthu, Dharmalingam; Latgé, Jean-Paul; Aimanianda, Vishukumar (Frontiers in Cellular and Infection Microbiology, 2021)
Although belong to the same genus, Aspergillus fumigatus is primarily involved in invasive pulmonary infection, whereas Aspergillus flavus is a common cause of superficial infection. In this study, we compared conidia (the infective propagules) of these two Aspergillus species. In immunocompetent mice, intranasal inoculation with conidia of A. flavus resulted in significantly higher inflammatory responses in the lungs compared to mice inoculated with A. fumigatus conidia. In vitro assays revealed that the dormant conidia of A. flavus, unlike A. fumigatus dormant conidia, are immunostimulatory. The conidial surface of A. fumigatus was covered by a rodlet-layer, while that of A. flavus were presented with exposed polysaccharides. A. flavus harbored significantly higher number of proteins in its conidial cell wall compared to A. fumigatus conidia. Notably, β-1,3-glucan in the A. flavus conidial cell-wall showed significantly higher percentage of branching compared to that of A. fumigatus. The polysaccharides ensemble of A. flavus conidial cell wall stimulated the secretion of proinflammatory cytokines, and conidial cell wall associated proteins specifically stimulated IL-8 secretion from the host immune cells. Furthermore, the two species exhibited different sensitivities to antifungal drugs targeting cell wall polysaccharides, proposing the efficacy of species-specific treatment strategies. Overall, the species-specific organization of the conidial cell wall could be important in establishing infection by the two Aspergillus species.